2016
DOI: 10.3758/s13414-016-1198-0
|View full text |Cite
|
Sign up to set email alerts
|

Task-relevant information is prioritized in spatiotemporal contextual cueing

Abstract: Implicit learning of visual contexts facilitates search performance-a phenomenon known as contextual cueing; however, little is known about contextual cueing under situations in which multidimensional regularities exist simultaneously. In everyday vision, different information, such as object identity and location, appears simultaneously and interacts with each other. We tested the hypothesis that, in contextual cueing, when multiple regularities are present, the regularities that are most relevant to our beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The effects on accuracy extend previous findings, suggesting that stimulus predictability improves performance only when predictions pertain to task-relevant targets [ 24 , 36 , 37 ]. Accordingly, the validity of cues predictive of the target location (latency) improved accuracy in the spatial (temporal) task ( Fig 1C ), but not vice versa.…”
Section: Discussionsupporting
confidence: 84%
“…The effects on accuracy extend previous findings, suggesting that stimulus predictability improves performance only when predictions pertain to task-relevant targets [ 24 , 36 , 37 ]. Accordingly, the validity of cues predictive of the target location (latency) improved accuracy in the spatial (temporal) task ( Fig 1C ), but not vice versa.…”
Section: Discussionsupporting
confidence: 84%
“…In the real world-for instance, in our commute-we may utilize only the portion of regularities that are currently relevant information (e.g., which café I will go to today, which space in the parking lot I should use this morning, and which part of the building I should head for), instead of representing all possible kinds of regularities that might not be immediately useful or might consist of too much abstract information (e.g., the sequence of the café, then the parking lot, and then the office building). Consistent with this idea, Higuchi, Ueda, Ogawa, and Saiki (2016) found that when statistical regularities were available in multiple dimensions (location and object identity), only the regularities that were most relevant to one's task goal were prioritized, suggesting that observers prioritized the most relevant information for statistical learning, instead of learning all kinds of statistical regularities.…”
Section: Discussionmentioning
confidence: 76%
“…That is, the pigeons should form object-location associations. Alternatively, if one of the features, such as location, is more salient than the other, such as object, as has been found in human studies (Endo & Takeda, 2004;Higuchi et al, 2016;Jiang & Song, 2005), then we might hypothesize that the same overshadowing of object information by location information will be observed in pigeons, in which case memory binding based on object-location associations should be prevented.…”
Section: Binding In Pigeonsmentioning
confidence: 87%